EMDR v. other psychological therapies for PTSD: a systematic review and individual participant data meta-analysis - Wright, Simonne Lesley; Karyotaki, Eirini; Cuijpers, Pim; Bisson, Jonathan; Papola, Davide; Witteveen, Anke; Suliman, Sharain; Spies, Georgina; Ahmadi, Khodabakhsh; Capezzani, Liuva; Carletto, Sara; Karatzias, Thanos; et al. (Psychological medicine, 2024)
This systematic review and individual participant data meta-analysis (IPDMA) examined the overall effectiveness of eye movement desensitization and reprocessing (EMDR) in reducing posttraumatic stress disorder (PTSD) symptoms, achieving response and remission, and reducing treatment dropout among adults with PTSD compared to other psychological treatments. Additionally, we examined available participant-level moderators of the efficacy of EMDR. This study included randomized controlled trials. Eligible studies were identified by a systematic search in PubMed, Embase, PsyclNFO, PTSDpubs, and CENTRAL. The target population was adults with above-threshold baseline PTSD symptoms. Trials were eligible if at least 70% of study participants had been diagnosed with PTSD using a structured clinical interview. Primary outcomes included PTSD symptom severity, treatment response, and PTSD remission. Treatment dropout was a secondary outcome. The systematic search retrieved 15 eligible randomized controlled trials (RCTs); 8 of these 15 were able to be included in this IPDMA (346 patients). Comparator treatments included relaxation therapy, emotional freedom technique, trauma-focused cognitive behavioral psychotherapies, and REM-desensitization. One-stage IPDMA found no significant difference between EMDR and other psychological treatments in reducing PTSD symptom severity ( = -0.24), achieving response ( = 0.86), attaining remission ( = 1.05), or reducing treatment dropout rates ( = -0.25). Moderator analyses found unemployed participants receiving EMDR had higher PTSD symptom severity at the post-test, and males were more likely to drop out of EMDR treatment than females. The current study found no significant difference between EMDR and other psychological treatments. We found some indication of the moderating effects of gender and employment status.